The spread of corruption and the problem of political division in Libya (Sebha University Conference Proceedings, 2022)
The international community is increasingly interested in corruption crimes. I consider their ‎danger to economic and social stability, and the value and moral systems in the world. We ‎see the international community addressing the dangers of spreading corruption, and this ‎is shown through what international organizations are doing. whose regulations and ‎regulations related to the prevention of this crime, combating the acts associated with it, ‎punishing its perpetrators, and activating the role of civil society in combating corruption. ‎Its role in combating corruption and identifying the causes and types of corruption, and ‎what are the mechanisms that are used in this field, and identifying the challenges that ‎hinder civil society institutions in carrying out their role in facing the dangers of corruption. ‎Corruption is a humanitarian and national task in which everyone participates. - Reducing ‎the unemployment rate and providing job opportunities in a way that secures stability for ‎all members of society. - Setting strict laws to impose penalties against the perpetrators of ‎corruption. - Working on most of the seminars and awareness programs, with a focus on ‎suppressing the religious scruples of the communit.